Entrepreneurship : starting an enterprise, having an innovation mindset - Go, Josiah; Escareal-Go, Chiqui (Quezon City, Philippines : Josiah and Coralina Go Foundation, Inc., 2018)
Entrepreneurship: Starting an Enterprise. Having an Innovation Mindset. Now a new theory of Entrepreneurial success and failure is shared on the Four Gates Model. Overview Starting an Enterprise. Having an Innovation Mindset. Now a new theory of Entrepreneurial success and failure is shared on the Four Gates Model. GATE 1: PREPARATION Money: How to raise funds and estimate your company's worthMentors: How to know the four different mentors you needModel: How to use a 1-page business model map to create your future GATE 2: MARKETING Mindset: How to innovate on demandMarket: How to quickly spot, screen and seize an opportunityMessage: 9 ways to create value GATE 3: EXECUTION Machineries: Why having too many bosses won't workMethods: How to determine strategy-critical processes in the value chainManagement Skills: How to design a plan to make your strategy come alive GATE 4: SELF-LEADERSHIP Moving Forward: How adversities help you become betterMission: Why what you sell should be different from what you doMastery: What is the one single weakness entrepreneurs should overcome
Part 1. Introduction to Entrepreneurship -- Part 2. Development of the Business Plan via a business Model -- Part 3. Business Implementation -- Part 4. The Daily journey.
Includes bibliographical references and index.
Keywords: ENTREPRENEURSHIP